Exploring Digital Government Trends: A Comprehensive Bibliometric and Systematic Review - Lubis, Sandi; Ahmad, Jamaluddin; Jovita, Hazel; Hardianti, Hardianti; Dema, Herman (Jurnal Studi Ilmu Pemerintahan, 2024)
This study presents a comprehensive bibliometric analysis of digital government research from 2014 to 2024, focusing on key trends, dominant subtopics, and implementation challenges. The research identifies a significant increase in publications, particularly during the COVID-19 pandemic, reflecting the heightened relevance of digital transformation in public administration. Key subtopics such as artificial intelligence, digital transformation, and smart governance dominate the field, showcasing the growing integration of advanced technologies in enhancing public services and governance. Despite these advancements, the study highlights persistent challenges, including inadequate technological infrastructure, regulatory lag, data security concerns, and digital inclusion disparities. These issues underscore the need for targeted investments, agile regulatory frameworks, and robust cybersecurity measures to ensure the successful and equitable implementation of digital government initiatives. The findings provide valuable insights for policymakers, practitioners, and researchers, emphasizing the importance of continued exploration of emerging technologies and strategies to overcome barriers to adoption. This study contributes to the existing literature by mapping the evolution of digital government research and offering guidance for future research and policy development in this critical area, aiming to enhance public service delivery and governance in the digital era.